Differentially methylated regions within lung cancer risk loci are enriched in deregulated enhancers. Issue 2 (1st February 2022) - Laplana, Marina; Bieg, Matthias; Faltus, Christian; Melnik, Svitlana; Bogatyrova, Olga; Gu, Zuguang; Muley, Thomas; Meister, Michael; Dienemann, Hendrik; Herpel, Esther; Amos, Christopher I.; Schlesner, Matthias; et al.
ABSTRACT: Genome-wide association studies (GWAS) have identified SNPs linked with lung cancer risk. Our aim was to discover the genes, non-coding RNAs, and regulatory elements within GWAS-identified risk regions that are deregulated in non-small cell lung carcinoma (NSCLC) to identify novel, clinically targetable genes and mechanisms in carcinogenesis. A targeted bisulphite-sequencing approach was used to comprehensively investigate DNA methylation changes occurring within lung cancer risk regions in 17 NSCLC and adjacent normal tissue pairs. We report differences in differentially methylated regions between adenocarcinoma and squamous cell carcinoma. Among the minimal regions found to be differentially methylated in at least 50% of the patients, 7 candidates were replicated in 2 independent cohorts (n = 27 and n = 87) and the potential of 6 as methylation-dependent regulatory elements was confirmed by functional assays. This study contributes to understanding the pathways implicated in lung cancer initiation and progression, and provides new potential targets for cancer treatment.